Compliance-gaining in policy announcement and willingness to co-produce: Experiment on psychosocial support policy - Siahaan, Timothy Pieter Christian (Magister Ilmu Administrasi Publik, 2024)
This article extends existing research on the determinants of willingness for co-production in policy by offering an additional lens through the use of compliance-gaining techniques in policy announcements. By experimenting on two different techniques in the case of a psychosocial support policy among Indonesian citizens, regression analysis results show that individuals will comply with policies, not necessarily because they are morally appealing, but because of other factors in the announcement. Data availability and simplified registration procedures are key components that boost compliance. On the contrary, individuals do not need to understand or have a mental health issue to participate in a segmented focus issue. Perceived legitimacy of public organizations, as well as motivation to contribute, continue to be prerequisites for highly effective public participation. This study concludes that a morally appealing delivery can be beneficial, but it requires accompanyment from other supporting aspects in the announcement, which encourages future research to test it within a specific socio-demographic background.